2012
DOI: 10.1371/journal.pone.0032755
|View full text |Cite
|
Sign up to set email alerts
|

CACNA1E Variants Affect Beta Cell Function in Patients with Newly Diagnosed Type 2 Diabetes. The Verona Newly Diagnosed Type 2 Diabetes Study (VNDS) 3

Abstract: BackgroundGenetic variability of the major subunit (CACNA1E) of the voltage-dependent Ca2+ channel CaV2.3 is associated to risk of type 2 diabetes, insulin resistance and impaired insulin secretion in nondiabetic subjects. The aim of the study was to test whether CACNA1E common variability affects beta cell function and/or insulin sensitivity in patients with newly diagnosed type 2 diabetes.Methodology/Principal FindingsIn 595 GAD-negative, drug naïve patients (mean±SD; age: 58.5±10.2 yrs; BMI: 29.9±5 kg/m2, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…PRKCQ belongs to Protein kinase C family which is required for the activation of NF-κB pathway. Upregulated gene Cacna1e is involved in the regulation of second-phase insulin release and the polymorphism of Cacna1e is associated with type 2 diabates [ 23 25 ]. The expression pattern of these upregulated genes were confirmed by the QPCR analysis using the samples from the MIN6 cells with FTO overexpression ( Fig 8A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRKCQ belongs to Protein kinase C family which is required for the activation of NF-κB pathway. Upregulated gene Cacna1e is involved in the regulation of second-phase insulin release and the polymorphism of Cacna1e is associated with type 2 diabates [ 23 25 ]. The expression pattern of these upregulated genes were confirmed by the QPCR analysis using the samples from the MIN6 cells with FTO overexpression ( Fig 8A ).…”
Section: Resultsmentioning
confidence: 99%
“…CACNA1E, one of the upregulated genes, encodes the voltage-dependent Ca(2+) channel Ca(V) 2.3. It has been reported this gene is involved in the regulation of second-phase insulin secretion and its polymorphism contributes to an increased risk of the development of type 2 diabetes [ 23 25 ]. Another upregulated gene, Ptpre, encoding protein tyrosine phosphatases, is a negative regulator of insulin receptor (IR) signaling and involved in the insulin-induced glucose metabolism through inactivation of IR [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are somewhat difficult to interpret, since mice of various ages (12-50 weeks) were used without appropriate age-matching or discrimination between male and female animals. The concept is nevertheless intriguing, as several studies have since linked variants in the gene encoding Ca v 2.3 channels to impaired glucose homeostasis in human T2DM patients [66][67][68]. Most notably, the region on chromosome 1q21-25, where the human Ca v 2.3 gene is located, has been linked to young-onset T2DM in Pima Indians [67].…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%
“…Ca V 2.3 is found to be highly expressed in neuronal cells and pancreatic beta cells. So far, three studies in different ethnic groups reported association of CACNA1E variants with type 2 diabetes 15 17 and investigation of molecular functions of the gene has been focused on pancreatic beta cells. 18 , 19 Our data for the first time suggest that Ca V 2.3 also plays a role in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%